The role of peat-forming bofedales in sustaining baseflow in the humid puna - Wyeth Wunderlich; Margaret Lang; Kristina Keating; Wilner Bandera Perez; Jasper Oshun (Journal of Hydrology: Regional Studies, 2023)
Study region: Humid puna of the Central Andes, Perú Study focus: Bofedales, or peat-forming wetlands, are a characteristic feature of the humid puna - a high elevation, seasonally dry grass- and shrub-land throughout the Central Andes. Despite the hydrologic importance of the humid puna for downstream communities, and the inference that bofedales play an important role, few studies have explored the hydrology of this ecosystem, and none have quantified bofedal water yield to streams. We designed a 3-year study in the Upper Ramuschaka Watershed (URW), a 2.12 km2 humid puna catchment sustaining a perennial stream used for irrigation downstream. We monitored hydrologic fluxes through the URW, periodically measured discharge in 19 nested subbasins across wet and dry seasons, and characterized the structure, hydraulic properties, and storage capacity of four bofedales. New hydrological insights for the region: Unit runoff is consistently higher in subbasins with greater bofedal coverage. High porosity peat fills in the wet season via groundwater recharge and drains slowly through underlying layers with low hydraulic conductivity. Bofedales cover 11.6% of the URW and store 105,000 ± 10,000 m3 of water seasonally. In the dry season, bofedales yield 49 ± 5 mm to streams, equivalent to 20 – 98% of the URW’s dry season runoff. Bofedales regulate drainage from the humid puna to downstream communities and are therefore vital to local and regional water security.